2019
DOI: 10.1186/s12871-019-0705-y
|View full text |Cite
|
Sign up to set email alerts
|

Relative cerebral hyperperfusion during cardiopulmonary bypass is associated with risk for postoperative delirium: a cross-sectional cohort study

Abstract: Background Our objective was to evaluate if changes in on-pump cerebral blood flow, relative to the pre-bypass baseline, are associated with the risk for postoperative delirium (POD) following cardiac surgery. Methods In 47 consecutive adult patients, right middle cerebral artery blood flow velocity (MCAV) was assessed using transcranial Doppler sonography. Individual values, measured during cardiopulmonary bypass (CPB), were normalized to the pre-bypass baseline value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
1
28
0
1
Order By: Relevance
“…In a recently published study by Thudium et al a relationship was found between cerebral hyperperfusion and post cardiac surgery delirium. In the study the authors examined right middle cerebral artery blood flow during CBP using the transcranial Doppler [21]. In our study we did not plan to measure cerebral blood flow, but the cardiac index during CBP was similar in both groups, with and without postoperative delirium (mean CI=2,5 l/min/m 2 , P=0.69).…”
Section: Discussionmentioning
confidence: 88%
“…In a recently published study by Thudium et al a relationship was found between cerebral hyperperfusion and post cardiac surgery delirium. In the study the authors examined right middle cerebral artery blood flow during CBP using the transcranial Doppler [21]. In our study we did not plan to measure cerebral blood flow, but the cardiac index during CBP was similar in both groups, with and without postoperative delirium (mean CI=2,5 l/min/m 2 , P=0.69).…”
Section: Discussionmentioning
confidence: 88%
“…Denault has recently proposed a modi ed NIRS algorithm in which ultrasound imaging plays a role in hemodynamic evaluation and cerebral imaging in case of increased intracranial pressure. (12) We suggest that ultrasound should become even more central in cerebral monitoring to con rm NIRS ndings and to evaluate cerebral hemodynamics.…”
Section: Discussionmentioning
confidence: 98%
“…This study stated that blood flow velocity changes and pulsatility play an important role in postoperative neurologic outcomes [ 6 ]. Thudium M. indicated that relative cerebral hyperperfusion also disrupts cerebral autoregulation and might play a significant role in dNCR development [ 4 ]. Individual values were normalized to the pre-bypass baseline value, and MCA BFV > 100% was defined as cerebral hyperperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have identified that neuropsychological complications emerge from insufficient cerebral perfusion [ 4 , 5 , 6 , 7 ]. Transcranial Doppler sonography (TCD) could provide information about middle cerebral artery (MCA) blood flow velocity (BFV) during surgery to detect hypoperfusion episodes and cerebral embolism.…”
Section: Introductionmentioning
confidence: 99%